Leishmania donovani infection induce Extracellular signal-regulated kinase ½ (ERK½) mediated lipid droplet generation in macrophages. (January 2022) - Banerjee, Somenath; Bose, Dipayan; Das, Subhadip; Chatterjee, Nabanita; Mishra, Snehasish; Das Saha, Krishna
Graphical abstract: Highlights: L. donovani ag83 induce LD generation in macrophages. ERK1/2 is responsible for LD generation. Neutralization of LD generation restores phago-lysosome biogenesis. Diminishing LD generation also correlated with augmentation of IL-12. Abstract: Recently unfolded mechanisms showed lipid droplet helps in pathogen survival and paralyzes host immune response. In the present study, we showed the extent of lipid droplet(LD) generation in Leishmania donovani infection, the signaling involved, and their function concerning pathogenicity. RAW 264.7 and J774A.1 cells were used to infect with L. donovani and then flow cytometry and confocal microscopy were used to detect lipid droplet generation and subsequent assays. In this study, we showed that L. donovani AG83 (AG83/MHOM/1983) triggers lipid droplet formation in macrophages in a time-dependent manner. We provide novel insight into the signaling molecules which is responsible for LD accumulation. Interestingly, LPG deficient attenuated Leishmania strain UR6 (UR6/MHOM/1978) failed to fuel LD generation. But inhibition of phagosome maturation drastically stimulates LD accumulation in UR6 infected MΦs. Aspirin treatment in AG83 infected MΦs does not only lower LD load but also favors phagolysosome biogenesis and corrects cytokine balance. Employing strategies to circumvent halt in phagosome maturation using drugs that manipulate lipid droplet generation could be used as a therapeutic tool to resist parasite growth in the early hour of infection.